Does the use of platelet-rich plasma in sinus augmentation improve the survival of dental implants? A systematic review and meta-analysis - Indumathi Sivakumar; Sivakumar Arunachalam; Muaiyed Mahmoud Buzayan; Jitendra Sharan (Elsevier, 2023)
Background: Platelet-rich plasma is considered an effective modality to promote bone regeneration, improve hard and soft tissue healing in surgical procedures including sinus augmentation. However, the survival of dental implants in sinus augmented sites with platelet-rich plasma has shown equivocal results in recent studies. Purpose: In this systematic review, data on dental implants' survival in sinus augmentation sites with platelet-rich plasma were examined. Materials and methods: Randomized controlled trials on the topic with a minimum mean follow-up of 6 months with no language restriction were considered. Other study designs on the topic were excluded. Accordingly, relevant articles were searched in Clinicaltrials.gov, Cochrane databases, PubMed/Medline, and Scopus up to April 2021. Using the Cochrane risk of bias assessment tool, the listed studies' risk of bias was evaluated. From the included studies, the pertinent information was taken and pooled for qualitative and quantitative analysis using R software 4.1.1. Results: Six randomized controlled trials involving 188 patients who underwent sinus augmentation with and without platelet-rich plasma, and 781 implants were included for qualitative and quantitative analysis. Four hundred and eleven implants were placed in the intervention group (with platelet-rich plasma) and 370 implants were placed in the control group (without platelet-rich plasma). The pooled estimate (OR 0.84, 95% CI 0.37 to 1.91; I2 = 0%) indicated that there was no statistically significant difference observed between the groups. The test for subgroup differences showed no statistically significant differences between the subgroups (p = 0.45) with no heterogeneity (I2 = 0%). Conclusion: The bias associated with selective reporting of outcome data was considered as some concern for bias. This systematic review revealed that the effect of platelet-rich plasma is uncertain on the survival of dental implants.